Measurement of the anisotropic thermal conductivity of carbon-fiber/epoxy composites based on laser-induced temperature field: Experimental investigation and numerical analysis. (December 2022) - Pawlak, Sebastian; Tokarski, Mieszko; Ryfa, Arkadiusz; Orlande, Helcio R.B.; Adamczyk, Wojciech
Abstract: In this paper, the authors proposed an inverse analysis using an in–house three-dimensional finite element method for the extraction of thermal conductivity tensor components of carbon-fiber/epoxy composite, based on the recorded thermographic data in the form of laser-induced temperature field. The core of the computational algorithm used for determining the thermal conductivity values (tensor components) consists of finite element solver, which operates in a hybrid mode with an analytical model. The presented method evaluates the thermal conductivity values by matching the calculated spatial and temporal temperature fields to the experimental data. Due to the specific nature of the measurement process and computational algorithm, the proposed technique is very efficient and allows for relatively rapid obtainment of the thermal conductivity values. For considered in this work composite material with 34% fiber volume fraction the experimental thermal conductivity values in transverse and parallel to the fiber directions were equal to 0.32 W/mK and 6.80 W/mK, respectively. Additionally, in order to verify the reliability of the presented methodology, the selected isotropic reference material was investigated, using the same testing procedure. The results obtained by using this novel approach are in good agreement with data measured using the conventional testing techniques.